Desire change: contemporary feminist art in Canada - Davis, Heather M. (Heather Margaret); Mentoring Artists for Women's Art (McGill-Queen's University Press, 2017)
"In the resistance to the violence of gender-based oppression, vibrant - but often ignored - worlds have emerged, full of nuance, humour, and beauty. Correcting a glaring omission of writing about contemporary feminist work by Canadian artists, Desire Change considers the resurgence of feminist art, thought, and practice in the past decade by examining artworks that respond to themes of diversity and desire. Essays by historians, artists, and curators present an overview of a range of artistic practices including performance, installation, video, textiles, and photography. Contributors address the desire for change through three central frames: how feminist art has significantly contributed to the complex understanding of gender as it intersects with sexuality and race; the necessary critique of patriarchy and institutions as they relate to colonization within the Canadian national-state; and the ways in which contemporary critiques are formed and expressed. The resulting collection addresses art through an activist lens to examine intersectional feminism, decolonization, and feminist institution building in a Canadian context. Heavily illustrated with representative works, Desire Change raises both the stakes and the concerns of contemporary feminist art, with an understanding that feminism is always and necessarily plural."-- Provided by publisher.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; canada; cours; discipline; femmes* artistes; féminisme décolonial; har4600; histoire de l'art; histoire et politique; intersectionnalité; patriarcat; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Making space for Indigenous feminism - Green, Joyce A. (Fernwood Publishing, 2017)
The 2007 first edition of this book proposed that Indigenous feminism was a valid and indeed essential theoretical and activist position, and introduced a roster of important Indigenous feminist contributors. The book has been well received nationally and internationally. It has been deployed in Indigenous Studies, Law, Political Science, and Women and Gender Studies in universities and appears on a number of doctoral comprehensive exam reading lists. The second edition, Making More Space, builds on the success of its predecessor, but is not merely a reiteration of it. Some chapters from the first edition are largely revised. A majority of the chapters are new, written for the second edition by important new scholars and activists. The second edition is more confident and less diffident about making the case for Indigenous feminism and in deploying a feminist analysis. The chapters cover issues that are relevant to some of the most important issues facing Indigenous people--violence against women, recovery of Indigenous self-determination, racism, misogyny, and decolonisation. Specifically, new chapters deal with Indigenous resurgence, feminism amongst the Sami and in Aboriginal Australia, neoliberal restructuring in Oaxaca, Canada's settler racism and sexism, and missing and murdered Indigenous women in Canada."-- Résumé de l'éditeur.
Keywords: amériques; approches et analyses; australie; canada; cours; discipline; droits des femmes*; droits des personnes autochtones; féminisme autochtone; histoire et politique; justice sociale; mexique; militance; océanie; patriarcat; pol4105; premier cycle; racisme; régions géographiques; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones; études décoloniales; études féministes

Au-delà du plaisir visuel: féminisme, énigmes, cinéphilie - Mulvey, Laura (Formes filmiques, 2017)
En 1975, Laura Mulvey publie Plaisir visuel et cinéma narratif, texte polémique qui met en lumière la manière dont la forme filmique serait structurée par l’inconscient de la société patriarcale. C’est l’essai fondateur des études féministes sur le cinéma. Rédigés entre 1975 et 2011, les textes choisis dans ce volume sont marqués par la redécouverte féministe de la psychanalyse et les transformations induites par le développement des technologies numériques. Qu’elle s’attache à des genres ou à des auteurs incontournables (le western, le mélodrame, Ophüls, Hitchcock, Godard), qu’elle incarne l’avènement d’un « spectateur pensif », qu’elle analyse les paradoxes de l’esthétique hollywoodienne ou la compilation de films de propagande coloniale, Laura Mulvey fait preuve d’une cinéphilie active et engagée.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; cinema hollywoodien; cinéma; com5170; communication; corps; cours; discipline; discours dominant; europe; har4600; histoire de l'art; histoire et politique; male gaze; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; regard masculin; royaume-uni; régions géographiques; sofia; systèmes d'oppressions; thématiques; théorie du cinéma; états-unis

Expertes en genre et connaissances féministes sur le développement. Qui sait ? - Verschuur, Christine (Graduate Institute Publications, L'Harmattan., 2017)
Depuis la quatrième Conférence mondiale sur les femmes à Beijing, on observe une forte augmentation du nombre de personnes expertes en genre. Celles-ci circulent, tout comme les pratiques, les idées, les théories et les textes féministes qui voyagent sont interprétés, resignifiés. Des inégalités existent dans les processus d’élaboration, la circulation et la traduction des savoirs. Le champ social constitué par les expertes en genre est ainsi traversé par des rapports de pouvoir. La notion de colonialité du pouvoir et des savoirs permet d’interroger l’hégémonie et l’autorité universelle des discours et des savoirs occidentaux. Les contributions des études féministes pour revisiter le développement sont soulignées dans cet ouvrage. Ces apports, énoncés depuis diverses perspectives, s’inscrivent dans des espaces de contestation de l’ordre mondial, sont nourris de la prise de conscience des multiples rapports de domination et de l’émergence de nouveaux mouvements sociaux. Ils participent d’un processus de décolonisation de la pensée féministe. Avec la collection « Genre et développement. Rencontres », nous poursuivons le dialogue de savoirs sur les questions féministes et de genre, la construction d’alliances et de ponts entre chercheur-es, organisations féministes et de recherche, ONG, organisations de coopération, expertes, aux Nords et aux Suds. Les textes, écrits par des chercheur-es ou personnes actives dans ces initiatives sont publiés dans leur langue originale.
Keywords: anthropologie; approches et analyses; discipline; féminisme décolonial; féminisme matérialiste; histoire et politique; patriarcat; projet charge mentale; pédagogie; racisme; ressource en ligne; science politique; science politique et droit; sciences humaines; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques